Junctional Bradikardia pada Pasien Hiperkalemia - Suwari, Cokorda Istri Padmi; Puradipa, Bayu; Wulandari, Ni Luh Eka Sriayu (Faculty of Medicine, Universitas Andalas, 2021)
Hyperkalemia is a life-threatening electrolyte abnormality resulting in cardiac arrhythmia. Hyperkalemia may also cause bradycardia with junctional rhythm. However, the prevalence of hyperkalemia accompanying symptomatic bradycardia has only been explored in a few case reports. Thus we present a case of hyperkalemia with uncommon ECG findings. It has been reported that a 76 years old woman with type 2 diabetes mellitus, hyperkalemia and suspected coronary artery disease complaining about palpitation. Electrocardiography (ECG) showed junctional bradycardia with tall T wave and laboratory examination showed mild hyperkalemia (5.8 mmol/L). After one day of observation, severe hypotension was detected. Unexpectedly the cardiac rhythm was returned into the sinus after correction of hyperkalemia using calcium gluconate, insulin, dextrose, and salbutamol. As serum potassium level rises, sinoatrial and atrioventricular conduction was blocked, causing escape rhythm (junctional escape rhythm). In hyperkalemia, cardiotoxicity can be caused by an increase in resting membrane potential, decreased depolarization and duration of depolarization. When detected on ECG, hyperkalemia should be treated urgently and important to identify underlying causes or precipitating factors of hyperkalemia. Sinus node dysfunction is not excluded in this case. Â Hyperkalemia can present a bradycardia junctional rhythm. Although the increasing serum potassium levels were low, hyperkalemia may have affected the conduction system leading to the ECG changes.Keywords: Â hyperkalemia, junctional bradycardia, symptomatic bradycardia